GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 23 Aug 2019, 23:59 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here. ### Request Expert Reply # If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

### Hide Tags

Manager  G
Joined: 27 May 2010
Posts: 200
If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

3
2
7 00:00

Difficulty:   85% (hard)

Question Stats: 49% (02:20) correct 51% (03:03) wrong based on 74 sessions

### HideShow timer Statistics

If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x) such that f2(J(f1(x))) = f3(x)

A) f1(x)
B) f3(x)/x
C) f3(x)
D) f2(x)
E) f2(x)/x
Senior Manager  P
Joined: 09 Jun 2014
Posts: 343
Location: India
Concentration: General Management, Operations
Re: If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

prashanths wrote:
If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x) such that f2(J(f1(x))) = f3(x)

A) f1(x)
B) f3(x)/x
C) f3(x)
D) f2(x)
E) f2(x)/x

Can someone please help me with approach of this problem.
I guess it involves F inverse.
Manager  G
Joined: 21 Feb 2019
Posts: 125
Location: Italy
Re: If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

3
$$f_2 (J(f_1)) = f_3$$

$$1 - J(\frac{1}{x}) = \frac{1}{1-x}$$

$$J(\frac{1}{x}) = - \frac{x}{1-x}$$

To get $$J(x)$$, you need to reverse $$x$$ to the power of negative 1. So you derive $$J(x) = \frac{1}{1- x}$$. Correct answer is C.
_________________
If you like my post, Kudos are appreciated! Thank you.

MEMENTO AUDERE SEMPER
Senior Manager  P
Joined: 09 Jun 2014
Posts: 343
Location: India
Concentration: General Management, Operations
Re: If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

lucajava wrote:
$$f_2 (J(f_1)) = f_3$$

$$1 - J(\frac{1}{x}) = \frac{1}{1-x}$$

$$J(\frac{1}{x}) = - \frac{x}{1-x}$$

To get $$J(x)$$, you need to reverse $$x$$ to the power of negative 1. So you derive $$J(x) = \frac{1}{1- x}$$. Correct answer is C.

Thanks Lucajava. I was missing this highligted text.
Director  P
Joined: 19 Oct 2018
Posts: 790
Location: India
If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

2
$$f_2(J(f_1(x)))= f_3(x)$$

$$1-J(\frac{1}{x})$$=$$\frac{1}{(1-x)}$$

$$J(\frac{1}{x})$$=$$\frac{-x}{(1-x)}$$

$$J(\frac{1}{x})$$= (1/x)/[1-(1/x)]

$$J(x)=\frac{x}{(1-x)}$$

prabsahi wrote:
prashanths wrote:
If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x) such that f2(J(f1(x))) = f3(x)

A) f1(x)
B) f3(x)/x
C) f3(x)
D) f2(x)
E) f2(x)/x

Can someone please help me with approach of this problem.
I guess it involves F inverse.
Manager  S
Joined: 11 Feb 2018
Posts: 74
Re: If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

lucajava wrote:
$$f_2 (J(f_1)) = f_3$$

$$1 - J(\frac{1}{x}) = \frac{1}{1-x}$$

$$J(\frac{1}{x}) = - \frac{x}{1-x}$$

To get $$J(x)$$, you need to reverse $$x$$ to the power of negative 1. So you derive $$J(x) = \frac{1}{1- x}$$. Correct answer is C.

Hi could you please elaborate on the solution. Unfortunately I am not following. I got the right answer by substitution functions one at a time but took 4+ minutes.
Manager  G
Joined: 21 Feb 2019
Posts: 125
Location: Italy
Re: If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

1
aliakberza wrote:
lucajava wrote:
$$f_2 (J(f_1)) = f_3$$

$$1 - J(\frac{1}{x}) = \frac{1}{1-x}$$

$$J(\frac{1}{x}) = - \frac{x}{1-x}$$

To get $$J(x)$$, you need to reverse $$x$$ to the power of negative 1. So you derive $$J(x) = \frac{1}{1- x}$$. Correct answer is C.

Hi, could you please elaborate on the solution. Unfortunately, I am not following it. I got the right answer by substitution functions one at a time but took 4+ minutes.

So, we are demanded to find out what is $$J(x)$$ such that $$f_2 (J(f_1(x))) = f_3(x)$$.

We know that $$f_2(x) = 1 - x$$. Thus, $$f_2(J(f_1(x)) = 1 - J(f_1(x)$$.

Now, knowing that $$f_1(x) = \frac{1}{x}$$, we can rewrite it as $$f_2(J(f_1(x)) = 1 - J(\frac{1}{x})$$.

Turn back to the original equation, and substitute what we've found into it: $$1 - J(\frac{1}{x}) = \frac{1}{1-x}$$.

After some computations, we derive $$J(\frac{1}{x}) = - \frac{x}{1-x}$$.

To get $$J(x)$$, you need to raise $$x$$ to the -1 power. In fact $$\frac{1}{x}^{-1} = x$$. Elaborating on this, what you find out is:

$$- \frac{x^{-1}}{1 - x^{-1}} = \frac{1}{x} * \frac{x}{x - 1} = \frac{1}{1 - x}$$.

I hope it's clear!
_________________
If you like my post, Kudos are appreciated! Thank you.

MEMENTO AUDERE SEMPER
Manager  G
Joined: 27 May 2010
Posts: 200
Re: If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

2
If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x) such that f2(J(f1(x))) = f3(x)

f2(J(f1(x))) = f3(x)

Since f2(x) = 1 - x and f3(x) = 1/(1-x)

f2(J(f1(x))) = 1 - J(f1(x)) = 1/(1-x)

Since f1(x) = 1/x,

J(1/x) = 1 - 1/(1-x) = -x/(1-x)

Substitute 1/x as x,

J(x) = - (1/x)/(1 - 1/x) = -(1/x)/((x-1)/x)

= 1/(1-x)

which equals f3(x).

Option C
_________________
Please give Kudos if you like the post
Manager  S
Joined: 03 Mar 2017
Posts: 112
Location: India
GMAT 1: 650 Q45 V34 Re: If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

when you simplify LHS you get
f2(j(1/x))=1-j(1/x)
1-j(1/x)=1/1-x
1-1/1-x=j(1/x)
j(1/x)=-1/(1/x)-1=1/1-(1/x)=f3
Manager  B
Joined: 07 May 2018
Posts: 66
Re: If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

lucajava wrote:
$$f_2 (J(f_1)) = f_3$$

$$1 - J(\frac{1}{x}) = \frac{1}{1-x}$$

$$J(\frac{1}{x}) = - \frac{x}{1-x}$$

To get $$J(x)$$, you need to reverse $$x$$ to the power of negative 1. So you derive $$J(x) = \frac{1}{1- x}$$. Correct answer is C.

How do you reverse x
Senior Manager  P
Joined: 09 Jun 2014
Posts: 343
Location: India
Concentration: General Management, Operations
Re: If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)  [#permalink]

### Show Tags

$$f_2(J(f_1(x)))= f_3(x)$$

$$1-J(\frac{1}{x})$$=$$\frac{1}{(1-x)}$$

$$J(\frac{1}{x})$$=$$\frac{-x}{(1-x)}$$

$$J(\frac{1}{x})$$= (1/x)/[1-(1/x)]

$$J(x)=\frac{x}{(1-x)}$$

prabsahi wrote:
prashanths wrote:
If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x) such that f2(J(f1(x))) = f3(x)

A) f1(x)
B) f3(x)/x
C) f3(x)
D) f2(x)
E) f2(x)/x

Can someone please help me with approach of this problem.
I guess it involves F inverse.
[/quote]

Thanks Nick!! Re: If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)   [#permalink] 20 Jul 2019, 21:20
Display posts from previous: Sort by

# If f1(x) = 1/x, f2(x) = 1 - x, f3(x) = 1/(1-x) then find J(x)

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

#### MBA Resources  